2008
DOI: 10.1039/b802581a
|View full text |Cite
|
Sign up to set email alerts
|

Chemcatcher® and DGT passive sampling devices for regulatory monitoring of trace metals in surface water

Abstract: This work aimed to evaluate whether the performance of passive sampling devices in measuring time-weighted average (TWA) concentrations supports their application in regulatory monitoring of trace metals in surface waters, such as for the European Union's Water Framework Directive (WFD). The ability of the Chemcatcher and the diffusive gradient in thin film (DGT) device sampler to provide comparable TWA concentrations of Cd, Cu, Ni, Pb and Zn was tested through consecutive and overlapping deployments (7-28 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 25 publications
0
52
1
Order By: Relevance
“…For short term studies, which include collection of composite samples over the deployment period or for sites with relatively stable and expressed concentration gradient of trace metals, high degrees of correlation were found between dissolved and DGT-labile concentrations. [22,24,33,40,44] In our study this was not the case. The only common characteristic for all metals was the lower average concentration of both dissolved and DGT-labile concentrations of trace metals at site SP2 compared to SP1 and SP3, over the duration of the study.…”
Section: Dgt-labile Concentrations Of Trace Metalscontrasting
confidence: 40%
See 1 more Smart Citation
“…For short term studies, which include collection of composite samples over the deployment period or for sites with relatively stable and expressed concentration gradient of trace metals, high degrees of correlation were found between dissolved and DGT-labile concentrations. [22,24,33,40,44] In our study this was not the case. The only common characteristic for all metals was the lower average concentration of both dissolved and DGT-labile concentrations of trace metals at site SP2 compared to SP1 and SP3, over the duration of the study.…”
Section: Dgt-labile Concentrations Of Trace Metalscontrasting
confidence: 40%
“…Such specific variability patterns clearly show the overall dynamics of trace metal concentrations at the study area, but also demonstrates that the discrete sampling methodology, most widely used in environmental monitoring programs and research studies, [2,3,37,38] is not ideal for (highly) dynamic aquatic systems. [39][40][41] Examining the entire 5-month period, specific trends of trace metal concentrations varied by metals and sites. There was no clear correlation (Pearson's coefficient; all samples/sites) found between the metals.…”
Section: Spatio-temporal Distribution Of Dissolved Trace Metalsmentioning
confidence: 99%
“…The diffusion process is influenced by water temperature and by hydrodynamic conditions (water turbulence) at the surface of the sampler. Comparisons between the Chemcatcher and DGT were undertaken by Allan et al (2008) in a 28-day trial during which fluctuating concentrations of metals (Cd, Cu, Ni, Pb, Zn) were observed in frequent spot samples. This study assessed the potential of these two devices for the regulatory monitoring of trace metals in surface water.…”
Section: Passive Samplers For Metalsmentioning
confidence: 99%
“…Comparisons between the Chemcatcher and DGT were undertaken in a 28 day trial during which fluctuating concentrations of metals (Cd, Cu, Ni, Pb, Zn) were observed in frequent spot samples. This study assessed the potential of these two devices for the regulatory monitoring of trace metals in surface water (Allan et al ., 2008). It demonstrated that the two sampling devices provided similar information, and were able to integrate concentrations reliably even where there were fluctuations in concentration during the deployment period.…”
Section: Metals and Radionuclidesmentioning
confidence: 99%